Protein tyrosine kinase 7 is essential for tubular morphogenesis of the Wolffian duct - Xu, Bingfang (2016)
The Wolffian duct, the proximal end of the mesonephric duct, undergoes non-branching morphogenesis to achieve an optimal length and size for sperm maturation. It is important to examine the mechanisms by which the developing mouse Wolffian duct elongates and coils for without proper morphogenesis, male infertility will result. Here we show that highly proliferative epithelial cells divide in a random orientation relative to the elongation axis in the developing Wolffian duct. Convergent extension (CE)-like of cell rearrangements is required for elongating the duct while maintaining a relatively unchanged duct diameter. The Wolffian duct epithelium is planar polarized, which is characterized by oriented cell elongation, oriented cell rearrangements, and polarized activity of regulatory light chain of myosin II. Conditional deletion of protein tyrosine kinase 7 (PTK7), a regulator of planar cell polarity (PCP), from mesoderm results in loss of the PCP characteristics in the Wolffian duct epithelium. Although loss of Ptk7 does not alter cell proliferation or division orientation, it affects CE and leads to the duct with significantly shortened length, increased diameter, and reduced coiling, which eventually results in loss of sperm motility, a key component of sperm maturation. In vitro experiments utilizing inhibitors of myosin II results in reduced elongation and coiling, similar to the phenotype of Ptk7 knockout. This data suggest that PTK7 signaling through myosin II regulates PCP, which in turn ensures CE-like of cell rearrangements to drive elongation and coiling of the Wolffian duct. Therefore, PTK7 is essential for Wolffian duct morphogenesis and male fertility.